ANALISIS STRUCTURE-CONDUCT-PERFORMANCE (SCP) PADA INDUSTRI KECIL DAN MENENGAH MAKANAN OLAHAN KOTA PEKANBARU (Studi Kasus Pada IKM Tahu di Kecamatan Payung Sekaki) - Pratama, Muda Restu; Kornita, Sri Endang; Pailis, Eka Armas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research carried out in the district of Payung Sekaki to the tofu small-medium industry. This Study aims to identify the structure, conduct and performance market are formed in the industry small-medium tofu that there are in the district Payung Sekaki. This research method is quanlitative deskriktif. Population in this study there was a total of 17 business units. Sampling for the determination of the study authors sensus method that is the entire population being sampled. Used data derived from primary data and secondary data obtained from the BPS and Departement of industry and Trade of the Pekanbaru city and then data directly from small-medium industry respondents tofu in district Payung Sekaki. Analysis tools used in this study is Market Share ,Concentration Ratio, Indeks Herfiendhal-Hircsman, Capital to Labour Ration and Price Cost Margin. This study has shown that the calculation of CR4 and IHH corresponding range in the can industry market structure in the district tofu is a monopolistic market structure with a CR4 value of 35,35% and IHH amounted to 562,82%.Conduct industry seen from CLR the results indicate that the value CLR is only about 2.846 % - 6.142 % this means that the conduct of small-medium industrial tofu in district Payung Sekaki is a capital intensive industry. The performance of industrial tofu can be seen from the PCM gained an average of 23,8 %. With the biggest PCM is 82.3 % but the biggest PCM does not become the largest (MS) market share means that the benefits seen from PCM does no affect the market share.Keywords : SCP, Tofu Small-Medium Industry, Pekanbaru City